Artificial photosynthesis on tree trunk derived alkaline tantalates with hierarchical anatomy: towards CO2 photo-fixation into CO and CH4. Issue 1 (10th October 2014) - Zhou, Han; Li, Peng; Guo, Jianjun; Yan, Runyu; Fan, Tongxiang; Zhang, Di; Ye, Jinhua
Abstract : Artificial photosynthesis is carried out on alkaline tantalates MTaO3 (M = Li, Na, K) with hierarchical anatomy derived from tree trunks using only artificial sunlight, water, and carbon dioxide as inputs to produce carbon monoxide and methane as outputs. Abstract : Artificial photosynthesis, the photochemical fixation and recycling of CO2 back to hydrocarbon fuels using sunlight and water, is both a significant challenge and an opportunity that, if realized, could have a revolutionary impact on our energy system. Herein, we demonstrate one of the first examples using biomass derived hierarchical porous photocatalysts for CO2 photo-fixation into sustainable hydrocarbon fuels. A generic method is proposed to build a series of alkaline tantalates MTaO3 (M = Li, Na, K) with hierarchical anatomy from macro- to nanoscales using activated carbonized tree trunks as templates. Artificial photosynthesis is carried out on MTaO3 series using only artificial sunlight, water, and carbon dioxide as inputs to produce carbon monoxide and methane as the main outputs. The CO2 photo-fixation performance can be enhanced by introducing a macropore network, which mainly enhances light transfer and accelerates gas diffusion. The research provides prototype models that integrate individual nanoscale components into higher level macroscopic artificial photosynthetic systems for better solar-to-fuel conversion efficiencies. This work would have potential significance for the ultimate construction of "artificial trees" and provide envisions creating "forests" of these CO2 -capturing artificial trees to remove carbon dioxide from the atmosphere and convert it into sustainable fuels.